2022
DOI: 10.3389/fcvm.2022.961979
|View full text |Cite
|
Sign up to set email alerts
|

Training intensity influences left ventricular dimensions in young competitive athletes

Abstract: BackgroundIn young athletes, exercise causes changes in the heart that include growth in wall thickness and mass of the left ventricle and expansion of the heart’s chambers. The heart’s function is either preserved or enhanced, but this may change to the opposite over time.ObjectiveThis study aimed to assess structural and functional cardiac adaptations in relation to exercise training time, intensity, and performance in young competitive athletes.MethodsA total of 404 children and adolescents (14.23 ± 2.0 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 70 publications
1
6
0
1
Order By: Relevance
“…39 Furthermore, decrements in E/A ratio were noted alongside increases in LV chamber size in adolescent athletes tracked over a 10-month period. 12 Unnithan et al, 20 using the same cohort of SP seen in this study demonstrated higher E and E′ during submaximal cycle ergometer exercise compared to CON when exercising at the same relative exercise intensity. These findings support the theory of a diastolic functional reserve for exercise in the SP.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…39 Furthermore, decrements in E/A ratio were noted alongside increases in LV chamber size in adolescent athletes tracked over a 10-month period. 12 Unnithan et al, 20 using the same cohort of SP seen in this study demonstrated higher E and E′ during submaximal cycle ergometer exercise compared to CON when exercising at the same relative exercise intensity. These findings support the theory of a diastolic functional reserve for exercise in the SP.…”
Section: Discussionsupporting
confidence: 61%
“…Evidence to support this latter contention was noted in elite, male endurance cyclists, whereby lower E and E′ velocities were identified compared to sub‐elite and nonathletes at rest supporting the theory of a diastolic functional reserve 39 . Furthermore, decrements in E/A ratio were noted alongside increases in LV chamber size in adolescent athletes tracked over a 10‐month period 12 . Unnithan et al., 20 using the same cohort of SP seen in this study demonstrated higher E and E′ during submaximal cycle ergometer exercise compared to CON when exercising at the same relative exercise intensity.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Weberruß et al found that a higher aerobic capacity significantly influences the thickness of the septal wall in diastole, as well as a higher training intensity influences the ventricular diameter in systole and diastole. ( Weberruß et al, 2022) With the use of the Cornell criterion it was found that no athlete from both groups present voltage criteria for the presence of LVH, however in a meta-analysis conducted by Zhigang You et al it was found that the LVH detected through this criterion has a higher predictive value in mortality from cardiovascular disease. This criterion was applied to the general population and it was found that 87% of the population had a higher risk for death from all causes, 66% had a higher risk for cardiovascular death and 70% had a higher risk for major cardiovascular events.…”
Section: Giamouzismentioning
confidence: 99%